The return of the muro: Institutional bricolage, customary institutions, and protection of the commons in Lembata Island, Nusa Tenggara - Nurhady Sirimorok; Asfriyanto Asfriyanto (Forestry Faculty, Universitas Hasanuddin, 2020)
The Lembata region is known for complex environmental conflicts between local institutions and external interests to protect endangered species such as the dugong and sperm whale. In this paper, we examine how the Tokajaeng community applies traditional rules (muro) in the face of environmental threats to the commons, such as depletion of forests and mangroves, and degradation of coral reefs. Critical Institutional Analysis is applied to examine institutional arrangements governing the commons. The approach acknowledges the complexity of institutions entwined in everyday social life, power relations that animate them, their socio-historical formation, and interplay between formal and informal institutions, as well as the convergence between modern and traditional arrangements. Fieldwork involved in-depth investigation on how the Tokajaengs create and applied rules (muro) and how they actively participated in the process of establishing new rules. We find that the muro responds reflexively to both internal and external dynamics in protecting the commons. They at once adapt to changes that threaten the commons in a way that each new threat corresponds with a new rule. Therefore, although the muro is a longstanding institution for local conservation, once suppressed for almost three decades during the New Order era, new arrangements have emerged since 2005 following political reforms in Indonesia. In the context of state efforts applying top-down conservation instruments, the muro shows the value of local institutional authority rooted in local belief systems that can take on new shapes through adaptive mechanisms. The muro therefore offers new opportunities for rethinking conservation in the Wallacea region, in ways that can actively engage local authority to devise and enforce rules to protect the environment.